Epithelioid Glioblastoma in A 15-Year-Old Boy: A Rare Case Report: Life Sciences -Pathology - Pandey, Dr.Poornima; Chawda, Dr.Hanish Kumar; Shah, Dr.Parth (International Journal of Life Science and Pharma Research, 2023)
Epithelioid glioblastoma (E-GBM), one of the rarest intrusive forms of Glioblastoma multiforme (GBM), was consigned in the World Health Organization (WHO) categorization of the Central nervous system (CNS) in the year 2016. The current article reports a rare epithelioid glioblastoma described for its histomorphological character and clinical finding for its medical rarity. The present case deals with a 15-year-old boy complaining of headaches and multiple episodes of vomiting. The investigatory procedures revealed hypo-intense multiple lesions in the left medial frontal lobe extending to a Sylvian fissure. The case is being discussed to distinguish the development of secondary glioblastomas, which usually occur due to pre-existing lesions, which were not present in our discussed case. The patient had come from a rural background with no previous investigations, ophthalmological examination revealed the presence of bilateral papilledema, and the hematological reports were within normal range. The patient was managed with magnetic resonance imaging (MRI) and computed tomography (CT), which depicted a multifocal tumor. Further left fronto temporal craniotomy and ablation of the lesion were done. The surgical procedure upshot divulged that the patient was conscious with improved right side weakness but a remnant motor aphasia, but within a short span, he could walk with support. The incidence of E-GBM that too in adolescent children is minuscule, and due to its poor prognosis, it's very crucial to acknowledge the attributable features of epithelioid glioblastoma, inclusive of functional outset, neuro-imaging, and the hazards of surgical measures.